ORIGIN OF GRAPHITE-COATED DIAMONDS FROM ULTRAHIGH-PRESSURE METAMORPHIC ROCKS - Korsakov A.V.; Shatsky V.S. (My University, 2004)
The occurrence of graphite-coated microdiamonds is a characteristic feature of ultrahigh-pressure metamorphic rocks. Nonetheless, their tiny dimension was an insurmountable obstacle for the study of these aggregates for a long time. Our observations show that graphite-coated diamonds were formed before their capture by the host mineral (garnet, clinopyroxene, zircon, and others). This fact is very important for the development of a genetic model. If we assume that crystallization of graphite is related to pressure decrease (i.e., graphite growth in the thermodynamic stability field), then the minerals with the graphite-coated diamond should be formed at the retrograde stage and they cannot characterize PT conditions corresponding to the peak of metamorphism.